ANALISIS TINGKAT KEMATANGAN LAYANAN TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK ITIL V4 PADA PMI PROVINSI SUMATERA SELATAN - Alyssa Hasyim; Arif Yulianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of information technology (IT) has significantly transformed organizational operational processes, including humanitarian organizations such as the Indonesian Red Cross (Palang Merah Indonesia/PMI). The implementation of IT through the Goods Management and Activity Reporting System at the South Sumatra PMI aims to improve the effectiveness of logistics management, documentation, and activity reporting processes. However, several challenges remain in its implementation, including system disruptions, limited feature optimization, and the lack of comprehensive evaluation of the quality of IT services provided. This study aims to analyze information technology service management in the Goods Management and Activity Reporting System at the South Sumatra PMI using the Information Technology Infrastructure Library (ITIL) version 4 framework. This research applies a qualitative approach with data collection techniques including observation, interviews, and documentation studies. The analysis is conducted based on ITIL V4 practices covering service management aspects, processes, technology, and human resources. The results of this study are expected to provide an overview of the effectiveness level of implemented IT services, identify obstacles in system management, and provide improvement recommendations to enhance information technology service quality. The implementation of ITIL V4 is expected to support PMI’s operational sustainability through more structured, efficient, and organization-aligned IT service management.